2023
DOI: 10.3389/fpubh.2022.1075204
|View full text |Cite
|
Sign up to set email alerts
|

Understanding older adults' intention to use patient-accessible electronic health records: Based on the affordance lens

Abstract: BackgroundGiven the aging population and the rapid development of the digital society, concerns about promoting older adults' health skills are increasing. Patient-accessible electronic health records (PAEHRs) are implemented globally for aging health safeguards. The demand for using health-related information communication technologies (ICTs) among older adults and the factors that promote their usage intention of PAEHRs need to be studied.MethodsDrawing upon affordance theory, we constructed a research model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…96,97 Among the solutions used, an online health record available to the patient and family has been introduced (it has been suggested that such a solution could become a useful tool for sharing health information), and patients have been monitored for the long-term impact of PAEHRs on their communication with health care professionals and engagement in the care process. 98 Nurgalieva et al analyzed patients' views on sharing their health data through PAEHRs and found that older patients and patients with lower levels of education were more likely to share their data. 99 Eriksson-Backa et al evaluated older adults' experiences of using the PAEHR portal and other electronic health services and found that improvements in security, usability, and additional 100 Another study found that patient-provider collaboration promotes the use of apps dedicated to older adults and empowers them to lead healthy lifestyles.…”
Section: The Older Patients As the Emrs Recipientsmentioning
confidence: 99%
“…96,97 Among the solutions used, an online health record available to the patient and family has been introduced (it has been suggested that such a solution could become a useful tool for sharing health information), and patients have been monitored for the long-term impact of PAEHRs on their communication with health care professionals and engagement in the care process. 98 Nurgalieva et al analyzed patients' views on sharing their health data through PAEHRs and found that older patients and patients with lower levels of education were more likely to share their data. 99 Eriksson-Backa et al evaluated older adults' experiences of using the PAEHR portal and other electronic health services and found that improvements in security, usability, and additional 100 Another study found that patient-provider collaboration promotes the use of apps dedicated to older adults and empowers them to lead healthy lifestyles.…”
Section: The Older Patients As the Emrs Recipientsmentioning
confidence: 99%